Hymenasplenium hovenkampii (Aspleniaceae), a new bipinnatisect fern species from Lesser Sunda Islands of Indonesia - Xu, Ke-Wang; Liu, Yu-Xuan; Chen, Yi-Fei; Zhang, Li-Bing (Phytotaxa, 2023)
A new species of Hymenasplenium (Aspleniaceae), H. hovenkampii, from the Lesser Sunda Islands of Indonesia is described. This species was preliminarily identified as H. unilaterale, but can be easily distinguished by its bipinnatisect laminae (vs. 1-pinnate lamina) and reddish brown (vs. dark brown to black) stipes and rachises. In fact, all species known so far in the genus have simple or 1-pinnate laminae, whereas the new species is the only one in the genus with bipinnatisect laminae.